KEBERADAAN DAN PERAN PEREMPUAN DALAM TARI TAMPURUANG DI NAGARI KOTO BARU KABUPATEN SOLOK SELATAN - Ningsih, Lisa Wahyu; Indrayuda, Indrayuda; Mansyur, Herlinda (SENDRATASIK UNP, 2019)
Abstract This study aimed to reveal and explain the existence and role of women in the Tampuruang dance in Nagari Koto Baru, South Solok regency. Besides, to reveal the role and reason why there must be a female dancer in the Tampuruang dance performed at the nagari Koto Baru until this time. This type of research was qualitative using descriptive methods. Data were obtained through direct observation and interviews, as well as documentation and literature studies. Data were analyzed based on the approach of Miles and Huberman, namely analyzing the phenomena that occur in Tampuruang dance performance activities and the phenomenon of women in Tampuruang dance. After collecting the data, it was collected, reduced, presented and verified and concluded. The results showed that the presence of women in Tampuruang dance became an important part of the performance. Also, women's activities are not only as dancers but also as musicians. Women are a symbol of sako and pusako holders and as a symbol of Bundo Kanduang, and as manager of internal family matters. Women are the owners of traditional houses that need to be highlighted in welcoming guests to the Koto Baru village. The reason for the need for women in the Tampuruang dance is as a dance icon and as a symbol of kinship matrilineal which symbolizes Bundo Kanduang as manager of household matters. Keywords: Tampuruang dance, female dancers, and roles.